Evaluation of Pain response experienced by the patients after normal teeth extraction according to the operator genders (Mustansiria Dental Journal, 2018)
Gender stereotypes can lead to a variety of generalizations that affect theperceptions of patients. Pain mechanism start with peripheral stimuli which willinitiate the afferent nerves fibers that will transmit the signals towards the centralnervous system through the spinal cord into the cerebral cortex where the pain signalwill be translated.The aim of this research is to evaluate the complex assessing of patient’s painperception in relation to the gender of the dentist during normal teeth extraction.Samples in this study was composed of (50) patients, divided into two equalgroups, first group treated by male students and the second’s group treated by femalestudents.The results of statistical analysis of data showed that pain perception by thepatients was in mild status more in male group 18(72%) than female group4(16%),While in moderate was less in male group 5(20%) than female group15(60%),and in sever also less in male group 2(8%) than female group 6 (24%).A significant difference was shown between the two students' gender in case ofmoderate and sever pain status (Chi-square in moderate status 8.33 & p-value= 0.004while in sever status 2.381 & 0.048respectively), while high significant difference inmild status (Chi-square15.91and P